+0  
 
+1
60
1
avatar+131 

If \(f(x) = x^2 - 3x + 4\), find the value of \(f(\sqrt3 - \sqrt2)\)

 Jun 29, 2023
edited by SportzGuy2310  Jun 29, 2023
 #1
avatar
+1

We have that f(x) = x^2 - 3x + 4. To find the value of f(sqrt(3) - sqrt(2)), we simply substitute sqrt(3) - sqrt(2) into the function for x. This gives us:

f(sqrt(3) - sqrt(2)) = (sqrt(3) - sqrt(2))^2 - 3(sqrt(3) - sqrt(2)) + 4

We can simplify this expression as follows:

= 3 - 3sqrt(2) + 3 - 3sqrt(3) + 4 = 10 - 3sqrt(2) - 3sqrt(3)

Therefore, the value of f(sqrt(3) - sqrt(2)) is 10 - 3sqrt(2) - 3sqrt(3).

Answer:

The value of f(sqrt(3) - sqrt(2)) is 10 - 3sqrt(2) - 3sqrt(3).

 Jun 29, 2023

3 Online Users

avatar
avatar